Simple Terrarium Teaching Aid for Guided Inquiry Learning Model: The Development of Learning Instruments to Students' Concept Understanding in Global Warming and Environmental Awareness - Najda Aliyatun Naezak; Erna Noor Savitri; Fidia Fibriana (Journal of Innovation in Educational and Cultural Research, 2021)
This research aims to determine the feasibility and characteristics of the guided inquiry learning model assisted by a simple terrarium on students' concept understanding and environmental awareness in the global warming topic of study. The research and development (RnD) methodby analysis, design, development, implementation, and evaluation (ADDIE) was performed. The data collection instruments used were observation sheets, expert validation sheets, and questions. The teaching and learning instruments were declared feasible and ready for application with a few revisions based on the validation results. The n-gain analysis of increasing students' conceptual understanding was in the high category at 0.76. The percentage of observations regarding environmental awareness increased at each successive meeting. The first meeting was 39.06%, the second meeting was 63.12%, and the third meeting was 89.37%. In conclusion, the guided inquiry learning model assisted by a simple terrarium is feasible to improve students' conceptual understanding and environmental virtue ethics.